Systematic Literature Review: The Influence of Budget Realization, HR Competency, and Organizational Characteristics on IKPA - Anggraini, Rachmarini Dian; Syahril Djaddang (Jurnal Ar Ro'is Mandalika (Armada), 2026)
State budget implementation represents the managerial capacity and integrity of the public bureaucracy in managing fiscal resources for the benefit of the public. The Indonesian government, through the Ministry of Finance, introduced the Budget Execution Performance Indicator (IKPA) as a quantitative-based measure of APBN implementation performance. However, several studies have demonstrated an empirical paradox: increased budget realization is not always accompanied by an increase in the IKPA value. This phenomenon confirms that non-financial factors such as human resource (HR) competence, organizational characteristics, and institutional legitimacy play a critical role in determining the effectiveness of budget implementation. This study used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method with a Systematic Literature Review (SLR) approach, analyzing twenty national scientific publications from 2020–2024. The analysis results indicate that HR competence and institutional support are the main determinants of IKPA success. This study emphasizes the importance of synergy between financial efficiency, HR professionalism, and institutional compliance in improving budget implementation performance in the public sector.